PROSPEK PENGEMBANGAN USAHA PEMBESARAN IKAN TOMAN (Channa micropeltes cuvier,1841) DI DESA MUARA MUNTAI ULU KECAMATAN MUARA MUNTAI KABUPATEN KUTAI KARTANEGARA - Siti Lutfiah; Said Abdusysyahid; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The purpose of this research is to know the development prospect of toman breeding business in Muara Muntai Ulu Village based on NVP, IRR, NB/CR criteria and continued with Pay Back Period analysis, and to know the level of sensitivity of toman fish enlargement in Muara Muntai Ulu Village. Sample method used in this research is census method with 10 respondents. This research was conducted in March to September 2017. Data analysis method used is financial feasibility analysis and sensitivity analysis The result of this research indicates that toman breeding (Channa micropeltes cuvier, 1841) in cages in Muara Muntai Ulu village is quite prospective and financially feasible to be continued and developed in the future based on NVP, IRR, NB/CR and Pay Back Period, level of sensitivity analysis indicates that the toman fish breeding effort is not feasible financially to be continued and developed if there is an increase of 506% totol cost, production turn to 84% and price down 84%.